St. Vincent and the Grenadines : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1994)
This report analyzes economic developments in St. Vincent and the Grenadines in the first half of the 1990s. Real GDP increased at an average annual rate of 5 percent in 1988-93, reflecting sustained growth in most sectors except for agriculture and manufacturing, which showed some volatility. In 1993, economic growth slowed to 1.4 percent as a sharp decline in agricultural production and in manufacturing activity only partly offset growth in the construction and tourism sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet